Cold War Broadcasting : Impact on the Soviet Union and Eastern Europe - Garton Ash, Timothy; Parta, R. Eugene, 1940-; Johnson, A. Ross (Book collections on Project MUSE., 2010)
Examines the role of Western broadcasting to the Soviet Union and Eastern Europe during the Cold War, with a focus on Radio Free Europe and Radio Liberty. It includes chapters by radio veterans and by scholars who have conducted research on the subject in once-secret Soviet bloc archives and in Western records. It also contains a selection of translated documents from formerly secret Soviet and East European archives, most of them published here for the first time. --Book Jacket.